Răspunsuri

2014-09-17T20:07:32+03:00
[(24 + 123 : 3 + a) : 6 : 6] * 3 + 254 = 554
[(24 + 123 : 3 + a) : 6 : 6] * 3 = 554 - 254
[(24 + 123 : 3 + a) : 6 : 6] * 3 = 300
(24 + 123 : 3 + a) : 6 : 6 = 300 : 3
(24 + 123 : 3 + a) : 6 : 6 = 100
(24 + 123 : 3 + a) : 6 = 100 * 6
(24 + 123 : 3 + a) : 6 = 600
24 + 123 : 3 + a = 600 * 6
24 + 123 : 3 + a = 3600
123 : 3 + a = 3600 - 24
123 : 3 + a = 3576
41 + a = 3576
a = 3576 - 41
a = 3535
1 5 1
2014-09-17T20:08:41+03:00
[(24+123:3+a):6:6]x3+254=554
[(24 + 123 : 3 + a) : 6 : 6] * 3 = 554 - 254
[(24 + 123 : 3 + a) : 6 : 6] * 3 = 300
(24 + 123 : 3 + a) : 6 : 6 = 300 : 3
(24 + 123 : 3 + a) : 6 : 6 = 100
(24 + 123 : 3 + a) : 6 = 100 * 6
(24 + 123 : 3 + a) : 6 = 600
24 + 123 : 3 + a = 600 * 6
24 + 123 : 3 + a = 3600
123 : 3 + a = 3600 - 24
123 : 3 + a = 3576
41 + a = 3576
a = 3576 - 41
a = 3535


1 5 1